Viral Suppression of RIPK1-Mediated Signaling - Darshika J. Udawatte (American Society for Microbiology, 2021)
ABSTRACT Receptor-interacting serine/threonine-protein kinase 1 (RIPK1) has emerged as a key upstream regulator of cell death and inflammation. RIPK1-mediated signaling governs the outcome of signaling pathways initiated by tumor necrosis factor receptor 1 (TNFR1), Toll-like receptor 3 (TLR3), TLR4, retinoic acid-inducible gene 1 (RIG-I)/melanoma differentiation-associated protein 5 (MDA-5), and Z-binding protein 1 (ZBP1) by signaling for NF-κB activation, mitogen-associated protein kinase (MAPK) and interferon regulatory factor 3/7 (IRF3/7) phosphorylation, and cell death via apoptosis and necroptosis. Both cell death and inflammatory responses play a major role in controlling virus infections. Therefore, viruses have evolved multifaceted mechanisms to exploit host immune responses by targeting RIPK1. This review focuses on the current understanding of RIPK1-mediated inflammatory and cell death pathways and multiple mechanisms by which viruses manipulate these pathways by targeting RIPK1. We also discuss gaps in our knowledge regarding RIPK1-mediated signaling pathways and highlight potential avenues for future research.